PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH DASAR - Rona Elviliza; Peni Yulita; Nurhizrah Gistituati; Rusdinal Rusdinal; Nellitawati Nellitawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The success of educationis greatly influenced by the quality of the learning process that takes place inschools, which is largely determined by the quality and performance of teachers. Teachersare the main actors in creating meaningful learning experiences forstudents. This studyaims to explore the influence of transformational leadershipexercised by school principals on teacher performance in primary schools through aliterature review. By collecting and analysingthe results of national and international studies over the last 10 (ten) years, this article presents a series of empirical evidence, conceptual frameworks,mediator/moderator factors, and practical implications for primary school management. The results of the study show that transformational leadership has a positive and significant effect on teacher performance — both directlyand indirectly through variables such as teacher motivation, school culture, self-efficacy,and work climate. The article concludes with recommendations for head teachers andeducation policymakers to improve teacher performance through atransformational leadership style, as well as notes on the limitations of the study and directions forfurther research.